2015
DOI: 10.1007/s13524-015-0393-2
|View full text |Cite
|
Sign up to set email alerts
|

Between Tradition and Modernity: Marriage Dynamics in Kyrgyzstan

Abstract: The demographic literature on union formation in post-communist Europe typically documents retreat from marriage and increase in cohabitation. However, sociological and anthropological studies of post-Soviet Central Asia often point to a resurgence of various traditional norms and practices, including those surrounding marriage, that were suppressed under Soviet rule. We engage these two perspectives on union formation by analyzing transition to first marriage in Kyrgyzstan both before and after the collapse o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 54 publications
1
38
1
2
Order By: Relevance
“…The pre-marriage characteristics are sociodemographic characteristics (age at marriage, ethnicity, number of siblings), proxy variables for labour market anity (years of education, an indicator for having more than 11 years of education, employment status one and two years prior to the marriage) and a proxy for the prevalence of traditional values (evolution of the marriage decision). With regard to the latter point, we distinguish between love marriage, arranged marriage, and bride capture with the latter two representing traditional values (Nedoluzhko and Agadjanian, 2015;Becker et al, forthcoming), which have potential implications for labour market outcomes of females.…”
Section: Discussion Of Instrument and Identifying Assumptionsmentioning
confidence: 99%
“…The pre-marriage characteristics are sociodemographic characteristics (age at marriage, ethnicity, number of siblings), proxy variables for labour market anity (years of education, an indicator for having more than 11 years of education, employment status one and two years prior to the marriage) and a proxy for the prevalence of traditional values (evolution of the marriage decision). With regard to the latter point, we distinguish between love marriage, arranged marriage, and bride capture with the latter two representing traditional values (Nedoluzhko and Agadjanian, 2015;Becker et al, forthcoming), which have potential implications for labour market outcomes of females.…”
Section: Discussion Of Instrument and Identifying Assumptionsmentioning
confidence: 99%
“…The share of love marriages clearly increased over this period, and the share of both kidnapped and arranged marriages decreased, especially in the most recent years. These trends are in line with Nedoluzhko and Agadjanian (2015). Female respondents were also asked about their own and their husband's ages at marriage, whether their parents received a bride price, whether they ever gave birth, and detailed information on their children.…”
mentioning
confidence: 88%
“…Nedoluzhko and Agadjanian (2015) conducted a nationally representative survey in 2011/12 among slightly more than 2,000 households. The authors reported that one third of marriages among Kyrgyz were the result of kidnappings; half of these marriages were of a non-consensual nature.…”
Section: Background: Kidnapping Of Brides In Kyrgyzstanmentioning
confidence: 99%
See 2 more Smart Citations